An examination of analysis and practices for wind band using Abracadabra by Frank Ticheli, Little Symphony for Winds by Franz Schubert/Arr. Verne Reynolds, and Chester: Overture for Band by William Schuman - Ebersole, Richard Wilbur (My University, 2025)
The following report provides a comprehensive analysis of two works for wind band and one small chamber work: Abracadabra by Frank Ticheli, Chester by William Schuman, and Little Symphony for Winds by Franz Schubert arranged by Verne Reynolds. This analysis contains information that would be necessary for a conductor’s rehearsal preparation and performance of the works. Biographical information about the composer, composition, and historical perspectives of the work itself are included alongside technical difficulties, stylistic concerns, and musical elements of each work. The form of each work, as well as suggested listening and rehearsal outlines are also highlighted within this report. In addition, a detailed score analysis grid as presented by Dr. Frank Tracz in Mark Walker’s book, The Art of Interpretation of Band Music is provided for all works examined. As the researcher, my mission statement of music education and guidelines for the selection of quality repertoire is also included. It is the intent that this report will aid conductors in making informed decisions regarding the selection, preparation, and performance of these works.
Keywords: Frank Ticheli; Franz Schubert; Verne Reynolds; William Schuman; Abracadabra; Chester